Інформаційна система обліку донорів центру плазми крові - Мічурін, І. Є. (ХНУРЕ, 2022)
Every day on Earth, someone desperately needs the help of a donor. The importance of donor plasma is difficult to overestimate: most drugs made from it have no artificial counterparts. Plasma сenters are facilities where donors can donate their blood plasma so that they can be used to make medicines. Modern technology will help the administration of the blood plasma center to effectively keep records of donations, the doctor - to form a referral for donations, and the donor - to reduce the time required to make a donation of blood plasma. Therefore, the development of an information system for accounting for donors of the blood plasma center is relevant.